Restful web APIs with spring LiveLessons : (sneak peek video training) - Long, Josh (LiveLessons., 2014)
"Overview RESTful Web APIs with Spring LiveLessons demonstrates how to write REST services, and manage, secure and consume them using Spring Boot. Description REST has enabled people to build mobile applications that capture our imagination, entertain us, and help us. REST has ushered in a generation of incredibly sophisticated, HTML5-powered browser applications. REST has also made it easier for organizations to adopt a service-oriented architecture with less friction. REST's flexibility, however, can also be its greatest weakness: as often as not there is no clear guidance on where to go and how to get there. What does it mean to deploy a REST service? How do you handle errors in a REST service? What's the easiest way to write a REST service? Spring Developer Advocate Josh Long discusses and demonstrates strategies for securing REST API access along with handling errors and versioning. These LiveLessons also cover how hypermedia and HATEOAS help you to deliver developer and consume friendly web services."--Resource description page.